2004
DOI: 10.1101/gad.291004
|View full text |Cite
|
Sign up to set email alerts
|

The Notch target genes Hey1 and Hey2 are required for embryonic vascular development

Abstract: The Delta-Notch signaling pathway plays a central role in the development of most vertebrate organs. The Hey family of bHLH transcription factors are direct targets of Notch signaling. Loss of Hey2 in the mouse leads to cardiac defects with high postnatal lethality. We have now generated a mouse Hey1 knockout that has no apparent phenotypic defect. The combined loss of Hey1 and Hey2, however, results in embryonic death after embryonic day 9.5 (E9.5) with a global lack of vascular remodeling and massive hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
485
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(517 citation statements)
references
References 47 publications
27
485
1
4
Order By: Relevance
“…54 However, despite this inhibitory effect on EC proliferation, Notch activation was still compatible with up-regulation of arterial EC markers, such as Hey-2, similar to what we and others documented in in vitro studies. 55,56 Shh has also been shown to support neuronal differentiation, 57 yet we did not observe the formation of neurons in our system despite the intrinsic ability of hMAPCs for neuronal differentiation, the latter of which requires a different cytokine cocktail ( Figure S1; Document S1).…”
Section: Discussionmentioning
confidence: 79%
“…54 However, despite this inhibitory effect on EC proliferation, Notch activation was still compatible with up-regulation of arterial EC markers, such as Hey-2, similar to what we and others documented in in vitro studies. 55,56 Shh has also been shown to support neuronal differentiation, 57 yet we did not observe the formation of neurons in our system despite the intrinsic ability of hMAPCs for neuronal differentiation, the latter of which requires a different cytokine cocktail ( Figure S1; Document S1).…”
Section: Discussionmentioning
confidence: 79%
“…Our investigation of Adam10 endothelial knockout mouse model explicitly demonstrates that Adam10 is essential for endocardial cushion formation, ventricular trabeculation, and vasculogenesis. The AEKO mice not only phenocopied the Notch1 and Notch targets knockouts (Krebs et al, 2000;Fischer et al, 2004;Timmerman et al, 2004;Limbourg et al, 2005;Grego-Bessa et al, 2007), but also showed downregulated expression of Notch target gene Snail and Bmp2 in the cardiac tissues. Because we delete Adam10 primarily in the endothelial cells, which are only small fraction of the total cardiac, the expression changes of Snail and Bmp2 could be more severe in Adam10 deficient endocardium.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] To evaluate this, FACS sorted Flk1 ϩ cells were differentiated with or without ␥-secretase inhibitor (GSI) to block Notch signaling. Compared with control cultures, GSI treatment did neither alter CD31 and ␣SMA expression levels ( Figure 4A) nor the numbers of CD31 ϩ cells analyzed by FACS.…”
Section: Inhibition Of Notch Signaling Overrides Vegf-driven Arterialmentioning
confidence: 99%
“…[7][8][9] Hey1 and Hey2 are two direct downstream genes of Notch signaling and both have been reported to promote arterial fate, possibly by upregulating EphrinB2 and inhibiting EphB4 expression. 10,11 In addition, VEGF upregulates both Dll4 and Notch1 in vitro and promotes arterial specification in vivo. [12][13][14] Conversely, the orphan nuclear receptor COUP-TFII has been postulated to repress Notch signaling in veins, establishing the first genetic determinant of venous cell fate.…”
mentioning
confidence: 99%